A new species of Procamallanus (Nematoda: Camallanidae) from Pacific eels (Anguilla spp.) - Moravec, Frantisek; Justine, Jean-Lou; Würtz, Jürgen; Taraschewski, Horst; Sasal, Pierre (The Journal of parasitology, 2006)
A new species of parasitic nematode, Procamallanus (Procamallanus) pacificus n. sp., is described from the stomach of the Pacific shortfinned eel, Anguilla obscura (type host), and from the speckled longfin eel, Anguilla reinhardtii, from northern New Caledonia (Melanesia, South Pacific); from Anguilla sp. (cf. obscura) from the Fiji Islands (Melanesia, South Pacific); and from the giant mottled eel Anguilla marmorata from Futuna Island (Wallis and Futuna Islands, Polynesia). Although a total of 450 nematodes were collected, all specimens were females; this suggests either an extremely rare occurrence of males or parthenogenetic reproduction in this species. Procamallanus pacificus differs markedly from all congeners from fish hosts in possessing a greater number (4-9) of caudal mucrons in the female and by other morphological features. This parasite might become a serious pathogen of cultured eels in the region of the South Pacific. Batrachocamallanus Jackson and Tinsley, 1995 is considered a junior synonym of Procamallanus Baylis, 1923, to which 2 species are transferred as Procamallanus occidentalis (Jackson and Tinsley, 1995) n. comb. and Procamallanus siluranae (Jackson and Tinsley, 1995) n. comb. One third-stage larva of Procamallanus (Spirocamallanus) sp. was also recorded from Anguilla sp. (cf. obscura) from the Fiji Islands.
Keywords: Female; Nematoda; Secernentea Infections; nemoci ryb; Anguilla; hlístice; Animals; Microscopy, Electron, Scanning; ženské pohlaví; zvířata; infekce hlísticemi podtřídy Secernentea; mikroskopie elektronová rastrovací; Fish Diseases